(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
The article analyzes and evaluates the role of peer collaboration and its types in the teaching process. This includes investigating different types of peer strategies which can utilize to promote language development. It can also emphasize offering students numerous opportunities to improve their language skills in an engaging, interactive environment.